1992
DOI: 10.1159/000111650
|View full text |Cite
|
Sign up to set email alerts
|

The Fate of Schwann Cells Transplanted in the Brain during Development

Abstract: Purified rat Schwann cells labeled with Hoechst 33342 fluorescent fluorochrome were transplanted into the brain of the newborn shiverer mouse. The grafted cells survived and were able to migrate through the host parenchyme. However, Schwann cell migration was restricted to the grafted hemisphere and to structures adjacent to the graft. With time, Hoechst labeled cells, present at the site of implantation or dispersed in the host parenchyme, decreased progressively in number. Instead, they concentrated along th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 14 publications
4
22
0
Order By: Relevance
“…OECs are also becoming increasingly easier to obtain from extracranial sources, such as from human peripheral olfactory tissue or from similar tissue in the nasal cavity of rodents (Lu et al, 2001(Lu et al, , 2002Franklin, 2002b), thus providing the attractive proposition of a patient having the opportunity to provide their own olfactory tissue for autologous transplantation. Furthermore, the available evidence supports the view that OECs are more likely to integrate into the CNS parenchyma after grafting to repair the injured or demyelinated spinal cord (Li et al, 1998;Lakatos et al, 2000) than are Schwann cells (Baron-Van Evercooren et al, 1992;Blakemore, 1992;Duncan and Milward, 1995), as suggested by Doucette (1990Doucette ( , 1995 several years ago. One possible explanation for the failure of Schwann cells to integrate as easily into the CNS parenchyma is that astrocytes are known perturb the neuron-Schwann cell interactions normally leading to myelination (Franklin et al, 1992;Guenard et al, 1994b), and these cell-cell interactions appear also to inhibit the migration of Schwann cells toward the site of injury (Fawcett and Asher, 1999).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…OECs are also becoming increasingly easier to obtain from extracranial sources, such as from human peripheral olfactory tissue or from similar tissue in the nasal cavity of rodents (Lu et al, 2001(Lu et al, , 2002Franklin, 2002b), thus providing the attractive proposition of a patient having the opportunity to provide their own olfactory tissue for autologous transplantation. Furthermore, the available evidence supports the view that OECs are more likely to integrate into the CNS parenchyma after grafting to repair the injured or demyelinated spinal cord (Li et al, 1998;Lakatos et al, 2000) than are Schwann cells (Baron-Van Evercooren et al, 1992;Blakemore, 1992;Duncan and Milward, 1995), as suggested by Doucette (1990Doucette ( , 1995 several years ago. One possible explanation for the failure of Schwann cells to integrate as easily into the CNS parenchyma is that astrocytes are known perturb the neuron-Schwann cell interactions normally leading to myelination (Franklin et al, 1992;Guenard et al, 1994b), and these cell-cell interactions appear also to inhibit the migration of Schwann cells toward the site of injury (Fawcett and Asher, 1999).…”
Section: Discussionsupporting
confidence: 56%
“…Cellular migration of Schwann cells within the CNS parenchyma is also limited. For example, when they are transplanted into the cerebral hemisphere of newborn shiverer mice, the migration is mostly confined to the vicinity of the graft; the grafted Schwann cells are also eventually extruded from the CNS parenchyma (Baron- Van Evercooren et al, 1992). It has been suggested that astrocytes inhibit the migration of Schwann cells within the parenchyma of the CNS (Fawcett and Asher, 1999).…”
Section: Are Oecs a Clinically Relevant Alternative To Schwann Cells?mentioning
confidence: 99%
“…Although not all studies have followed Schwann cell survival for the time period of this study, it is generally believed that Schwann cells, once in the CNS, form a stable population ( Baron-Van Evercooren et al, 1992). The displacement of Schwann cells in the present model is therefore surprising, and the mechanism underlying this event remains to be determined.…”
Section: Long-term Viability Of Schwann Cells In the Spinal Cordmentioning
confidence: 76%
“…For Schwann cells to be considered as a viable therapy for central demyelinating conditions, in addition to being capable of remyelinating large areas of the cord (Scolding et al, 1998), they would have to restore debilitating motor functional deficits of the type resulting from large-scale demyelination. Finally, after remyelinating CNS axons, Schwann cells have to be capable of long-term survival in the CNS to ensure permanent recovery of function, an issue that remains unresolved ( Baron-Van Evercooren et al, 1992;Dusart et al, 1992).…”
mentioning
confidence: 99%
“…A number of cell types, including oligodendrocyte progenitors (Duncan et al, 1988;Keirstead et al, 1999Keirstead et al, , 2005Cao et al, 2005), Schwann cells (Blakemore and Crang Baron-Van Evercooren et al, 1992;Honmou et al, 1996), OECs (Franklin et al, 1996;Imaizumi et al, 1998;Barnett et al, 2000;Kato et al, 2000;Sasaki et al, 2004), and neural stem cells (Brustle et al, 1999;Akiyama et al, 2001), have been used to remyelinate central axons. However, an important prerequisite for recovery of action potential conduction in remyelinated axons is the appropriate organization of ion channels at nodes of Ranvier.…”
Section: Discussionmentioning
confidence: 99%